1987
DOI: 10.1271/bbb1961.51.93
|View full text |Cite
|
Sign up to set email alerts
|

Threonine production by co-existence of cloned genes coding homoserine dehydrogenase and homoserine kinase in Brevibacterium lactofermentum.

Abstract: The homoserine kinase (HK) gene was cloned from Brevibacterium lactofermentum M-15, a threonine-producing mutant. Then, a trimethoprim-resistant hybrid plasmid pAJ2 12 expressing the HK gene was constructed. A threonine-producing recombinant strain harboring pAJ210, a chloramphenicol-resistant plasmid on which homoserine dehydrogenase (HD) gene was cloned, was transformed further with the obtained HK-expressing plasmid pAJ2 12. Plasmids pAJ2 10 and pAJ212were compatible in B. lactofermentum because these two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The hom gene codes for homoserine dehydrogenase, and alleles of this gene, such as HomG378E [hom(Fbr)], that code for a dehydrogenase which is no longer feedback-inhibited by L-threonine have been identified (34). The overexpression of hom and thrB with high-copy-number plasmids is possible (13,29), whereas hom(Fbr) thrB can only be expressed at low levels (35). This is due to the resulting high internal L-threonine concentration of up to 100 mM, versus less than 1 mM in the wild type.…”
mentioning
confidence: 99%
“…The hom gene codes for homoserine dehydrogenase, and alleles of this gene, such as HomG378E [hom(Fbr)], that code for a dehydrogenase which is no longer feedback-inhibited by L-threonine have been identified (34). The overexpression of hom and thrB with high-copy-number plasmids is possible (13,29), whereas hom(Fbr) thrB can only be expressed at low levels (35). This is due to the resulting high internal L-threonine concentration of up to 100 mM, versus less than 1 mM in the wild type.…”
mentioning
confidence: 99%
“…Santamaria et al have found that pBL1 of B. lactofermentum is compatible with pCC1 of C. callunae [40]. It was also observed by Morinaga et al that pBL1‐ and pHM1519‐derived plasmids are compatible with each other [41]. In this case, the pBL1‐derived plasmid pAJ 212 was more stably maintained in the host than pAJ 210, a pHM1519 derivative, in the absence of selective pressure, and the latter is gradually lost.…”
Section: Plasmid Incompatibilitymentioning
confidence: 75%
“…However, there is an incompatibility problem when two plasmids are constructed with the same vector system and introduced into a bacterial cell. The plasmid co-existence system, as-employed in this paper using two different vectors, can be applied to similar purposes, one of which has been the breeding of a threonine producer of B. lactofermentum by Morinaga et al (1987).…”
Section: Discussionmentioning
confidence: 99%